Pengembangan Usaha Kerupuk Ibu Hamidah di Dusun Lekong Dendek Desa Dasan Tereng Kecamatan Narmada, Kabupaten Lombok Barat - Baiq Ertin Helmida; Baiq Kisnawati; Lalu Mimbar; Satriawan; Faizatul Fajariah; Gina Septiani Putri; Aliya Azimatu Zahra; Baiq Deria Ayuning Fatika (Valid Jurnal Pengabdian, 2026)
This community service activity was conducted in Lekong Dendek Dusun, Dasan Tereng Desa, Narmada Kecamatan. The objectives of the activity were to: 1) enhance the motivation and entrepreneurial mindset of business owners, fostering a business development orientation; 2) improve business management capabilities through the implementation of better management practices; and 3) upgrade the quality of product packaging and labeling to increase value-added and market competitiveness. The implementation methods employed included outreach sessions, training, demonstrations, hands-on practice, and mentoring. Monitoring and evaluation were conducted to assess the extent to which the partners implemented the provided material. The program results were as follows: 1) an increase in motivation and entrepreneurial mindset among business owners; 2) improved business management skills, particularly regarding the importance of simple bookkeeping, separating business and personal finances, calculating production costs, and determining selling prices; 3) enhanced packaging and label quality, resulting in a more attractive and informative appearance for the *kerupuk* (cracker) products, along with clearer product identity; 4) the participatory approach combining outreach, training, and mentoring—proved effective in increasing partners' knowledge and skills while fostering behavioral changes in business management; and 5) the service activity provided tangible benefits to the partners, serving as an initial step toward professionalizing business management and strengthening the competitiveness of MSMEs in Dasan Tereng Desa.